Conductive paste, electronic component, and laminate ceramic capacitor
A conductive paste with specific additives and composition addresses thermal contraction issues in multilayer ceramic capacitors, ensuring gradual sintering and reducing delamination and cracking, thus improving capacitor reliability and manufacturing efficiency.
Patent Information
- Application Number
- JP2023110358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Existing multilayer ceramic capacitors face issues of delamination and cracking during the firing process due to rapid thermal contraction of conductive films, which is exacerbated by the use of smaller conductive powders, leading to non-uniform dispersion of barium titanate and increased manufacturing costs.
A conductive paste composition comprising conductive powder, ceramic powder, binder resin, and organic solvent, with specific additives like phosphoric acid, is used to reduce the difference in thermal shrinkage between the conductive film and dielectric layer, ensuring gradual sintering and minimizing delamination and cracking.
The conductive paste effectively reduces thermal shrinkage differences, suppressing delamination and cracking during the sintering process, thereby enhancing the reliability and manufacturing efficiency of multilayer ceramic capacitors.
Smart Images

Figure 2025008310000009 
Figure 2025008310000010 
Figure 2025008310000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste, an electronic component, and a multilayer ceramic capacitor. [Background technology]
[0002] As electronic devices such as mobile phones and digital devices become smaller and more powerful, there is a demand for smaller electronic components, including multilayer ceramic capacitors, with higher capacitance. Multilayer ceramic capacitors have a structure in which a plurality of dielectric layers and a plurality of internal electrode layers are alternately laminated, and by making these dielectric layers and internal electrode layers thinner, the size of the capacitors can be reduced and their capacitance increased.
[0003] For example, a multilayer ceramic capacitor is manufactured as follows. First, a conductive paste for internal electrodes is printed in a predetermined electrode pattern on the surface of a green sheet (substrate) containing a dielectric powder such as barium titanate (BaTiO3) and a binder resin, and then dried to form a dry film (conductive film). The conductive paste contains conductive powder such as nickel. Next, the conductive film and the green sheet are alternately laminated to obtain a laminate. Next, this laminate is integrated by heat and pressure bonding to form a pressure-bonded body. This pressure-bonded body is cut, and an organic binder removal process is performed in an oxidizing atmosphere or an inert atmosphere, and then sintered to obtain a sintered chip. Next, a paste for external electrodes is applied to both ends of the sintered chip, and after sintering, nickel plating or the like is performed on the surface of the external electrodes to obtain a multilayer ceramic capacitor.
[0004] In the above-mentioned firing process to obtain a fired chip, if there is a large difference in the thermal shrinkage rate between the conductive film and the green sheet adjacent to the conductive film, the conductive film may delaminate from the green sheet, or a crack may occur in the laminate (conductive film or green sheet) that is pressed. In this case, the obtained multilayer ceramic capacitor may not have the desired electrical characteristics.
[0005] For example, Patent Document 1 discloses a paste-like conductor-forming composition that includes core-shell particles having a particle size of 100 nm to 1000 nm based on SEM observation, which are composed of nickel particles as core particles and a shell in which the surface of the nickel particles is coated with barium titanate, and a dispersion medium. Patent Document 1 states that thermal shrinkage can be suppressed by using a shell in which the surface of the nickel particles as core particles is coated with barium titanate.
[0006] Patent Document 2 discloses a nickel microparticle-containing composition that contains the following components A and B: A) first nickel microparticles having an average particle size in the range of 60 to 150 nm and a particle size variation coefficient of 0.2 or less as determined by scanning electron microscopy, and B) second nickel microparticles having an average particle size in the range of 10 to 60 nm and a particle size variation coefficient of 0.2 or less as determined by scanning electron microscopy, and a 5% heat shrinkage temperature that is 50° C. or more higher than the 5% heat shrinkage temperature of the first nickel microparticles. Patent Document 2 aims to suppress heat shrinkage by mixing the first nickel particles with second nickel particles having a small particle size and a high heat shrinkage temperature, and further coating the particles with elemental sulfur or by containing elemental phosphorus or nickel carbide. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2016-014194 A [Patent Document 2] JP 2014-145117 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, in Patent Document 1, the process includes a step of coating nickel particles with barium titanate, a step of adjusting the pH of the fine particles, and a step of evaporating the dispersion medium by heat treatment, so there is a risk that the nickel particles will link together or aggregate during the manufacturing process. If the nickel particles aggregate, the aggregates may penetrate the green sheet during compression bonding, causing a short circuit. In addition, the barium titanate will not be uniformly dispersed, decreasing the dielectric constant. Furthermore, if customization is required, such as changing the amount of barium titanate to match the thermal shrinkage rate of the green sheet, the manufacturing cost will be high.
[0009] Furthermore, in Patent Document 1, the nickel particles coated with barium titanate have a thermal shrinkage behavior measured by thermomechanical analysis (TMA) that is similar to the thermal shrinkage behavior of barium titanate particles (dielectric powder), thereby suppressing the occurrence of cracks that occur when the internal electrode layers are fired.
[0010] In Patent Document 2, two types of nickel particles are required, which increases the manufacturing cost. In addition, when the nickel particles are coated with elemental sulfur or treated to contain elemental phosphorus or nickel carbide in order to increase the sintering initiation temperature, the surface condition changes, which causes a problem of changing the dispersion behavior.
[0011] In addition, in Patent Document 2, the thermal shrinkage of mixed particles obtained by mixing two types of nickel particles having different average particle sizes is reduced, and the sintering start temperature (5% thermal shrinkage temperature measured by TMA) is increased, thereby making it possible to prevent defects such as delamination and cracks from occurring during sintering.
[0012] In recent years, in order to meet the demands of miniaturization and high capacity of multilayer ceramic capacitors, efforts have been made to make both the dielectric layer and the internal electrode layer thinner, and the diameter of the respective materials, BaTiO3 powder and conductive powder (e.g. nickel powder), is being made smaller. In particular, when the particle size of the conductive powder is made smaller, the difference in thermal contraction with the dielectric layer during the sintering process during manufacturing is more likely to increase compared to nickel powder, which has a larger particle size. Therefore, there is a demand for further reduction in the occurrence of delamination and cracks during the sintering process.
[0013] The inventors conceived the idea that one of the factors causing delamination and cracks in the firing process is a sudden increase in thermal shrinkage of the conductive film during firing, and as a result of extensive research, they discovered that by using a conductive paste having a specific composition, it is possible to reduce the difference between the thermal shrinkage behavior of the conductive film and the thermal shrinkage behavior of the dielectric layer, and to suppress the sudden thermal shrinkage of the conductive film during sintering, i.e., to reduce the thermal shrinkage difference (e.g., difference in thermal shrinkage rate) of the conductive film per temperature difference during sintering, and to suppress the occurrence of delamination and cracks, thereby completing the present invention.
[0014] In view of the above circumstances, the present invention aims to provide a conductive paste that can reduce the thermal shrinkage difference (difference in dimensional change rate) during sintering of a conductive film containing a conductive powder, without the need for special treatment of the conductive powder. [Means for solving the problem]
[0015] A first aspect of the present invention is a conductive paste comprising a conductive powder, a ceramic powder, an additive, a resin and an organic solvent, the conductive paste comprising, as the additive, a phosphoric acid-based additive having a structure represented by the following structural formula (1) in an amount of 0.05 mass% or more and 1.5 mass% or less relative to the total amount of the conductive paste, the organic solvent comprising a terpene-based solvent (a) and one or more solvents (b) selected from a hydrocarbon-based solvent, an acetate-based solvent, an ether-based solvent, and a ketone-based solvent, and the resin comprising at least one of a cellulose-based resin and an acetal-based resin.
[0016] [ka]
[0017] (However, R 1 contains at least one of an alkyl group having 6 or more carbon atoms, an ether group having 6 or more carbon atoms, a polyether group, and a polyester group; R 2 , R 3 are each independently hydrogen or an ammonium salt group, or contain at least one of an alkyl group, an ether group, and an ester group.
[0018] The conductive powder preferably has an average particle size of 0.05 μm or more and 1.0 μm or less. The conductive powder preferably contains at least one metal powder selected from Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof. The ceramic powder is preferably contained in an amount of 1 mass% or more based on the total amount of the conductive paste. The ceramic powder preferably contains barium titanate. The ceramic powder preferably has an average particle size of 0.01 μm or more and 0.5 μm or less. The conductive paste preferably further contains an acid dispersant and / or a base dispersant. The conductive paste is preferably for use as an internal electrode of a multilayer ceramic component.
[0019] In a second aspect of the present invention, there is provided an electronic component formed using the above-mentioned conductive paste.
[0020] In a third aspect of the present invention, there is provided a multilayer ceramic capacitor having at least a laminate in which dielectric layers and internal electrode layers are laminated, the internal electrode layers being formed using the above-mentioned conductive paste. Effect of the Invention
[0021] The conductive paste of the present invention can reduce the difference in thermal shrinkage of a conductive film manufactured using the conductive paste during firing without any special treatment of the conductive powder. Also, the multilayer ceramic capacitor of the present invention can suppress the occurrence of delamination and cracks during firing by forming internal electrodes using the conductive paste. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a perspective view and a cross-sectional view showing a multilayer ceramic capacitor according to an embodiment. [Diagram 2] FIG. 2 is a graph showing the thermal shrinkage curve obtained by thermomechanical analysis (TMA) measurement of Example 1. [Diagram 3] FIG. 3 is a photograph, substituted for a drawing, showing an image of a cross section of the evaluation pellet of Example 1 at 800° C. when fired, taken with a SEM (scanning electron microscope). [Figure 4] FIG. 4 is a drawing-substitute photograph showing an image of a cross section of the evaluation pellet of Comparative Example 1 when fired at 800° C., taken by SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] [Conductive paste] The conductive paste according to the embodiment includes a conductive powder, a ceramic powder, an additive, a binder resin, and an organic solvent. Each component will be described in detail below.
[0024] (conductive powder) The conductive powder is not particularly limited, and a metal powder can be used, for example, one or more powders selected from Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof. Among these, from the viewpoints of conductivity, corrosion resistance, and cost, Ni or its alloy powder (hereinafter, sometimes referred to as "nickel powder") is preferable. As the Ni alloy, for example, an alloy of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt, and Pd can be used. The Ni content in the Ni alloy is, for example, 50 mass% or more, preferably 80 mass% or more. In addition, the nickel powder may contain about several hundred ppm of element S in order to suppress rapid gas generation due to partial thermal decomposition of the binder resin during the binder removal process.
[0025] In addition, when nickel powder is used as the conductive powder, the manufacturing method is not particularly limited, and it can be manufactured using a conventionally known wet method or dry method. For example, the nickel powder may be nickel powder manufactured by a so-called dry method such as a CVD method, an evaporation quenching method, or a hydrogen reduction method using nickel salt or nickel hydroxide, or may be nickel powder manufactured by a so-called wet method such as a wet reduction method using a reducing agent such as hydrazine for a nickel salt solution. Among them, it is preferable to use nickel powder manufactured by a so-called wet method such as a wet reduction method. In addition, in the conductive paste of this embodiment, the nickel powder does not need to have a coating layer as in Patent Document 1.
[0026] The average particle size of the conductive powder is preferably 0.01 μm or more and 1.0 μm or less, more preferably 0.01 μm or more and 0.5 μm or less, and even more preferably 0.05 μm or more and 0.4 μm or less. When the average particle size of the conductive powder is within the above range, it can be suitably used as an internal electrode paste for a thin-film multilayer ceramic capacitor (multilayer ceramic component). In addition, the average particle size of the conductive powder may be, for example, 0.3 μm or less, 0.25 μm or less, or 0.2 μm or less. In the conductive paste of this embodiment, even if the average particle size of the conductive powder is within the above range, the thermal contraction difference during firing can be sufficiently reduced.
[0027] The average particle size is a value determined by observation with a scanning electron microscope (SEM), and is the average value (SEM average particle size, number average) obtained by measuring the particle size of each of multiple particles in an image observed with an SEM at 10,000 times magnification.
[0028] The content of the conductive powder is preferably 30% by mass or more and less than 70% by mass, more preferably 40% by mass or more and 60% by mass or less, based on the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0029] (ceramic powder) The ceramic powder is not particularly limited, and for example, in the case of a paste for an internal electrode of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected depending on the type of multilayer ceramic capacitor to be applied. As the ceramic powder, for example, a perovskite oxide containing Ba and Ti can be used, and preferably contains barium titanate (BaTiO3).
[0030] The ceramic powder may be a ceramic powder containing barium titanate as a main component and oxides as subcomponents. Examples of oxides include oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb, and one or more rare earth elements. The ceramic powder may be a perovskite-type oxide ferroelectric ceramic powder in which the Ba and Ti atoms of barium titanate (BaTiO3) are replaced with other atoms, such as Sn, Pb, and Zr.
[0031] When used as a conductive paste for internal electrodes, the ceramic powder may be powder of the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic capacitor (electronic component). This further suppresses the occurrence of cracks due to the difference in thermal contraction at the interface between the dielectric layer and the conductive film in the sintering process. In addition to the above, such ceramic powders include oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element)2O3, TiO2, and Nd2O3. Note that one type of ceramic powder may be used, or two or more types may be used.
[0032] The average particle size of the ceramic powder is, for example, 0.01 μm to 0.5 μm, preferably 0.01 μm to 0.3 μm. When the average particle size of the ceramic powder is in the above range, it is possible to form a sufficiently fine, thin, and uniform internal electrode when used as an internal electrode paste. The average particle size is a value determined by observation with a scanning electron microscope (SEM), and is the average value (SEM average particle size, number average) obtained by measuring the particle size of each of a plurality of particles from an image observed with an SEM at a magnification of 50,000 times.
[0033] The content of the ceramic powder is, for example, 1 mass % or more with respect to the entire conductive paste. By including a large amount of ceramic powder, the thermal shrinkage behavior of the conductive film can be made closer to that of the green sheet. The upper limit of the content of the ceramic powder may be 20 mass % or less, 10 mass % or less, 6 mass % or less, 4 mass % or less, 3 mass % or less, or 2 mass % or less. The smaller the content of the ceramic powder, the more the continuity of the conductive film is improved, and the higher the capacitance of the capacitor can be. Even if the content of the ceramic powder is reduced, the conductive paste of the present embodiment can reduce the difference in thermal shrinkage of the conductive film during sintering and reduce the difference in thermal shrinkage behavior with the green sheet.
[0034] The content of the ceramic powder is preferably 2 parts by mass or more relative to 100 parts by mass of the conductive powder. The content of the ceramic powder may be 20 parts by mass or less, 12 parts by mass or less, 8 parts by mass or less, 6 parts by mass or less, or 4 parts by mass or less relative to 100 parts by mass of the conductive powder.
[0035] (binder resin) The binder resin includes at least one of a cellulose-based resin and an acetal-based resin. When used as an internal electrode paste, from the viewpoint of improving the adhesive strength with the green sheet, the paste may include an acetal-based resin, or the acetal-based resin may be used alone. The acetal-based resin preferably includes a butyral-based resin, and more preferably includes polyvinyl butyral (PVB). When the conductive paste includes an acetal-based resin, the difference in thermal shrinkage behavior with the green sheet can be made smaller.
[0036] The content of the acetal resin may be, for example, 20% by mass or more, 40% by mass or more, or 60% by mass or more, based on the total amount of the binder resin. When the content of the acetal resin is within the above range, the adhesiveness is further improved, and the adhesive strength between the dry film and the green sheet (substrate) is improved.
[0037] The upper limit of the content of the acetal resin is not particularly limited, but may be, for example, 90% by mass or less, 80% by mass or less, or 50% by mass or less, based on the total binder resin. When the content of the acetal resin is within the above range, the conductive paste has an appropriate hardness, so that problems such as the printed film not peeling off from the support film and the electrodes being crushed during thermocompression bonding are unlikely to occur.
[0038] The weight average molecular weight (Mw) of the acetal resin may be 30,000 or more and 300,000 or less, 50,000 or more and 200,000 or less, or 100,000 or more and 150,000 or less. The glass transition temperature Tg of the acetal resin may be 50°C or more and 90°C or less, or 60°C or more and 80°C or less. By including an additive described later in addition to the acetal resin having the above characteristics, a conductive paste with improved adhesion can be obtained. The acetal resin may be used alone or in combination of two or more kinds.
[0039] Examples of the cellulose-based resin include methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, etc. When the cellulose-based resin is contained, the solubility in a solvent and the combustion decomposition property are good. Among the cellulose-based resins, ethyl cellulose is preferable.
[0040] For example, when a cellulose-based resin is included as a binder resin, the weight average molecular weight (Mw) may be 10,000 to 300,000, 30,000 to 250,000, or 50,000 to 200,000. The hydroxyl value of the cellulose-based resin is not particularly limited, but is preferably 0.1 mgKOH / g to 15 mgKOH / g, more preferably 0.5 mgKOH / g to 7 mgKOH / g, and even more preferably 1.5 mgKOH / g to 3 mgKOH / g. The cellulose-based resin may be included alone or in combination of two or more kinds.
[0041] The content of the cellulose-based resin is not particularly limited, but may be, for example, 20% by mass or more, 40% by mass or more, or 60% by mass or more, based on the total content of the binder resin. In addition, when the binder resin contains a cellulose-based resin and an acetal-based resin, the binder resin may contain 20% by mass or more, 40% by mass or more, or 60% by mass or more, based on the total content (100% by mass) of the cellulose-based resin and the acetal-based resin. When the contents of both resins are within the above range, the conductive paste can have an appropriate hardness, and defects such as the printed film not peeling off from the support film and the electrode being crushed during thermocompression bonding are unlikely to occur. In addition, the thermal shrinkage of the conductive film during firing can be made gentle, and the adhesiveness between the conductive film and the green sheet and the dispersibility of the conductive powder can be improved in a well-balanced manner. In addition, the upper limit of the content of the cellulose-based resin is not particularly limited, and may be less than 100% by mass, 90% by mass or less, or 80% by mass or less.
[0042] The binder resin may contain other resins such as acrylic resins in addition to the cellulose-based resin and the acetal-based resin.
[0043] The content of the binder resin is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 7% by mass, based on the entire conductive paste. When the content of the binder resin is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0044] The content of the binder resin is preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 14 parts by mass or less, relative to 100 parts by mass of the conductive powder.
[0045] (Organic solvent) As the organic solvent, a known organic solvent capable of dissolving the binder resin can be used. The organic solvent preferably contains a terpene-based solvent (a) and one or more solvents (b) selected from a hydrocarbon-based solvent, an acetate-based solvent, an ether-based solvent, and a ketone-based solvent. By containing these organic solvents, the compatibility with the binder resin is excellent, the dispersibility of the filler is excellent, and the sheet attack on the green sheet can be suppressed.
[0046] Examples of the terpene solvent (a) include dihydroterpineol, terpineol, dihydroterpinyl acetate, and the like, and among these, dihydroterpineol is preferred.
[0047] Examples of the hydrocarbon solvent (b1) include solvents containing tridecane, nonane, cyclohexane, etc., mineral spirits, naphthenic solvents, etc. Among them, it is preferable to contain mineral spirits. The content of the hydrocarbon solvent may be 10% by mass or more and 50% by mass or less, or 20% by mass or more and 40% by mass or less, based on the total organic solvent.
[0048] Examples of the acetate solvent (b2) include isobornyl acetate, isobornyl propionate, isobornyl butyrate, and isobornyl isobutyrate; glycol ether acetates such as ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol methyl ether acetate, 3-methoxy-3-methylbutyl acetate, and 1-methoxypropyl-2-acetate; glycol diacetates such as propylene glycol diacetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, and 1,6-hexanediol diacetate; and cyclohexanol acetate.
[0049] Examples of the ether solvent (b3) include propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; ethylene glycol ethers such as diethylene glycol mono-2-ethylhexyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol monohexyl ether, and ethylene glycol monohexyl ether; dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl-n-butyl ether, and dipropylene glycol dimethyl ether.
[0050] Examples of the ketone-based solvent (b4) include methyl isobutyl ketone, diisobutyl ketone, etc. When a ketone-based solvent is contained, it is possible to adjust the viscosity without impairing the dispersibility, and it is possible to improve the drying property.
[0051] The content of the organic solvent (total) is preferably 20% by mass or more and 60% by mass or less, more preferably 25% by mass or more and 45% by mass or less, based on the total amount of the conductive paste. When the content of the organic solvent is within the above range, the conductive paste has excellent conductivity and dispersibility. The content of the ether-based solvent is preferably 30% by mass or less.
[0052] The content of the organic solvent is preferably 50 parts by mass or more and 130 parts by mass or less, more preferably 60 parts by mass or more and 90 parts by mass or less, relative to 100 parts by mass of the conductive powder. When the content of the organic solvent is within the above range, the conductive powder has excellent conductivity and dispersibility.
[0053] In addition, the organic solvent may be one type of each type of solvent, or two or more types may be used. The organic solvent may include, for example, a terpene solvent (a) and a hydrocarbon solvent (b1), or may include dihydroterpineol (a) and mineral spirits (b1). When the terpene solvent (a) and the hydrocarbon solvent (b1) are included, it is preferable that the terpene solvent (a) is included in an amount of 60% by mass to 80% by mass, and the hydrocarbon solvent (b1) is included in an amount of 40% by mass to 20% by mass, based on the total amount of the organic solvent.
[0054] The organic solvent may include at least three kinds of organic solvents, for example, a terpene solvent (a), a hydrocarbon solvent (b1), and an acetate solvent (b2). Specifically, the organic solvent may include dihydroterpineol (a), mineral spirits (b1), and diethylene glycol monobutyl ether acetate (b2), or may include dihydroterpineol (a), mineral spirits (b1), and isobornyl acetate (b2). When these organic solvents are included, in addition to the above-mentioned effects, the surface smoothness of the dried film is further improved, and the dispersibility of the conductive paste is improved. When at least three types of solvents, namely, the terpene-based solvent (a), the hydrocarbon-based solvent (b1), and the acetate-based solvent (b2), are contained, it is preferable that the terpene-based solvent (a) is contained in an amount of 30 mass% to 70 mass%, the hydrocarbon-based solvent (b1) is contained in an amount of 40 mass% to 20 mass%, and the acetate-based solvent (b2) is contained in an amount of 30 mass% to 10 mass%, relative to the total amount of organic solvents (100 mass%).
[0055] (Additives)
[0056] (a) Phosphate-based additives The conductive paste according to this embodiment contains, as an additive, a phosphoric acid-based additive having a structure represented by the following formula (1).
[0057] [ka]
[0058] In the above formula (1), R1 contains at least one of an alkyl group having 6 or more carbon atoms, an ether group having 6 or more carbon atoms, a polyether group, and a polyester group; R 2 , R 3 are each independently hydrogen or an ammonium salt group, or contain at least one of an alkyl group, an ester group, and an ether group.
[0059] R 1 R includes at least one of an alkyl group having 6 or more carbon atoms, an ether group having 6 or more carbon atoms, a polyether group, and a polyester group. 1 It is preferable that the polyether group and polyester group are included. Examples of the polyether group include those having oxyalkylene such as oxymethylene, oxyethylene, and oxypropylene as a repeating unit. The polyether group and polyester group may have a polyether structure and a polyester structure, and may contain other structures. The alkyl group and ether group may each have one or more methylenes substituted with oxygen, and a part of the hydrogen atoms constituting the alkyl group and ether group may each be substituted with a substituent. The polyether group and polyester group may have a carbon number of 6 or more.
[0060] R 2 , R 3 R are each independently hydrogen or an ammonium salt group, or contain at least one of an alkyl group, an ester group, and an ether group. 2 , R 3 may be hydrogen. The ammonium base may be an alkyl ammonium base. The alkyl group, ester group, and ether group may have one or more methylenes substituted with oxygen, and some of the hydrogen atoms constituting the alkyl group, ester group, and ether group may be substituted with a substituent. For example, some of the hydrogen atoms constituting the alkyl group may be substituted with a phosphate ester group. 2 , R 3 may each independently be a hydrogen atom, an alkyl group, an ammonium salt group, or an alkyl phosphate group.
[0061] The additive may also include a phosphoric acid-based additive having one or more structures selected from the following formulas (2) and (3).
[0062] [ka]
[0063] [ka]
[0064] In the above formulas (2) and (3), R 1 each independently contains at least one of an alkyl group having 6 or more carbon atoms, an ether group having 6 or more carbon atoms, a polyether group, and a polyester group; R 2’ is hydrogen, an ammonium base, an alkyl group, or an alkyl phosphate group. 1 The preferred range of R in the above formula (1) is 1 is the same as:
[0065] When the conductive paste contains the phosphoric acid-based additive, the difference in thermal contraction of the conductive film is reduced when the pressed body of the conductive film and the green sheet is sintered, and the sintering of the conductive film proceeds relatively slowly. Although the details of the reason for this are unclear, it is thought that, for example, the phosphoric acid ester inhibits the combustion of the binder resin and forms a carbonized layer, which raises the temperature at which the binder resin completely decomposes.
[0066] The weight average molecular weight of the phosphoric acid additive is preferably 200 or more and 3000 or less. When the molecular weight of the phosphoric acid additive is in the above range, the difference in thermal shrinkage behavior with the green sheet is smaller. The lower limit of the weight average molecular weight of the phosphoric acid additive may be, for example, 200 or more, 300 or more, 500 or more, or 1000 or more. When the lower limit of the weight average molecular weight of the phosphoric acid additive is in the above range, the thermal shrinkage difference is reduced and the dispersibility may be further improved. The upper limit of the weight average molecular weight of the phosphoric acid additive may be 2500 or less, 2300 or less, or 2000 or less.
[0067] The content of the phosphoric acid additive is preferably 0.03% by mass or more and 1.5% by mass or less with respect to the entire conductive paste. When the content of the phosphoric acid additive is within the above range, the sinterability is good and the difference in thermal shrinkage behavior between the conductive film and the ceramic green sheet is small. The content of the phosphoric acid additive may be 0.1% by mass or more with respect to the entire conductive paste from the viewpoint of further reducing the difference in thermal shrinkage. The content of the phosphoric acid additive is preferably 1% by mass or less, more preferably 0.8% by mass or less with respect to the entire conductive paste from the viewpoint of the sinterability of the conductive film and the influence of the decomposition of the additive on thermal shrinkage. The content of the phosphoric acid additive may be 0.5% by mass or less, or may be 0.3% by mass or less. If the amount of the phosphoric acid additive is too large, the sintering behavior may be excessively delayed.
[0068] (b) Dispersant When the conductive paste contains a dispersant, the dispersibility of the conductive powder and the ceramic powder can be improved. The dispersant may contain, for example, an acid dispersant, a base dispersant, a nonionic dispersant, an amphoteric dispersant, etc., and preferably contains at least one of an acid dispersant and a base dispersant, and more preferably contains an acid dispersant. In addition, the base dispersant may not be contained. Note that these dispersants may be used alone or in combination of two or more.
[0069] The acid dispersant may include a carboxylic acid dispersant such as a higher fatty acid, a polycarboxylic acid dispersant, an acid dispersant having an acidic group such as a polymer surfactant, etc., and preferably includes a polycarboxylic acid dispersant. The polycarboxylic acid dispersant may be a comb-shaped carboxylic acid having a comb structure.
[0070] The higher fatty acid may be an unsaturated carboxylic acid or a saturated carboxylic acid, and is not particularly limited, but examples thereof include stearic acid, oleic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, linolenic acid, and other higher fatty acids having 11 or more carbon atoms. Of these, oleic acid or stearic acid is preferred.
[0071] The acid dispersant may be, for example, oleoyl sarcosine, which is a compound of glycine and oleic acid, or an alkyl monoamine salt type amide compound using a higher fatty acid such as stearic acid or lauric acid instead of oleic acid.
[0072] In addition, from the viewpoint of further improving the effect of suppressing separation between the conductive powder and the ceramic powder, a dicarboxylic acid may be included. The dicarboxylic acid is a carboxylic acid having two carboxyl groups (COO- groups). The average molecular weight of the dicarboxylic acid is not particularly limited, but may be, for example, 200 or more and 1000 or less.
[0073] Examples of the basic dispersant include aliphatic amines such as laurylamine, rosinamine, cetylamine, myristylamine, and stearylamine. When the conductive paste contains the acid dispersant and the basic dispersant, the conductive paste may have better dispersibility and viscosity stability over time.
[0074] The dispersant is contained in an amount of, for example, 0.01% by mass or more and 3% by mass or less with respect to the entire conductive paste. The upper limit of the content of the dispersant may be 2% by mass or less, 1% by mass or less, or 0.7% by mass or less. When the content of the dispersant is within the above range, the dispersibility of the conductive paste can be improved and sheet attack can be suppressed. When the content of the dispersant is high, the difference in thermal contraction behavior with the dielectric increases. However, in this embodiment, since the phosphoric acid-based additive is contained, even when the content of the dispersant is high, the difference in thermal contraction of the conductive film during sintering can be reduced, and the difference in thermal contraction behavior with the dielectric can be reduced.
[0075] (c) Other additives The conductive paste of the present embodiment may contain other additives in addition to the above components, as necessary. As the other additives, for example, conventionally known additives such as a defoamer, a plasticizer, a surfactant, and a thickener can be used.
[0076] (Characteristics of conductive paste) (a) Surface roughness The conductive paste according to this embodiment is applied to a substrate with an applicator to a wet film thickness of 10 μm, and dried at 120° C. for 10 minutes to obtain a dry film having a surface roughness (Sa) of 0.10 μm or less, 0.07 μm or less, or 0.05 μm or less. The surface roughness Sa (arithmetic mean roughness) of the dry film is also one of the indices showing the dispersibility of the conductive paste. The lower limit of the surface roughness Sa is not particularly limited, but a value exceeding 0 and a smaller value are preferable.
[0077] [Method of manufacturing conductive paste] The method for producing the conductive paste according to the present embodiment is not particularly limited, and a conventionally known method can be used. For example, the conductive paste can be produced by stirring and kneading the above-mentioned components with a three-roll mill, a ball mill, a mixer, a high-pressure homogenizer, or the like.
[0078] [Heat shrinkage behavior] The present inventors have conducted extensive research to solve the above problems, and have found that a conductive paste containing a conductive powder, a ceramic powder, an additive, a resin, and an organic solvent, having a specific composition, can suppress a rapid dimensional change during sintering of a conductive film made using the conductive paste, including cases in which the particle size of the conductive powder is small, i.e., can reduce the difference in thermal shrinkage, and have completed the present invention.
[0079] Conventionally, it was believed that if the difference between the thermal shrinkage start temperature (sintering start temperature) of the conductive powder and the thermal shrinkage start temperature (sintering start temperature) of the green sheet is large, the thermal shrinkage difference due to sintering occurs in a wider temperature range. Therefore, as shown in Patent Document 1 and the like, conventionally, it has been attempted to bring the thermal shrinkage start temperature of the conductive powder closer to the thermal shrinkage start temperature of the ceramic dielectric. For example, cracks are caused by gas generated when organic matter is decomposed during binder removal processing. In addition, cracks may occur due to the decomposition of remaining organic matter during firing processing and the thermal shrinkage difference due to sintering of the conductive powder, but the effect of organic matter on the thermal shrinkage of the conductive film has not been paid attention to so far.
[0080] However, in recent years, the conductive powder used in the conductive paste has been made smaller in particle size, which has lowered the thermal shrinkage start temperature of the conductive film. The conductive paste of this embodiment not only raises the thermal shrinkage start temperature to directly bring the thermal shrinkage behavior of the conductive film closer to that of the green sheet, but also reduces the thermal shrinkage difference of the conductive film in a specific temperature range during sintering, allowing the sintering reaction to proceed slowly and reducing the occurrence of delamination and cracks. When the conductive paste has the above composition, the sintering of the conductive film proceeds slowly, thereby suppressing the occurrence of delamination and cracks. Conventionally, in order to bring the thermal shrinkage behavior of the conductive film closer to that of the green sheet, ceramic powder (dielectric powder) such as barium titanate used in the green sheet has been added to the conductive paste, but in the case of the conductive paste of this embodiment, the amount of ceramic powder added can also be reduced.
[0081] (a) Difference in thermal shrinkage rate during firing For example, when the thermal shrinkage (dimensional change) of evaluation pellets produced by the conductive paste of this embodiment using the following method is measured using a thermomechanical analyzer (TMA), the difference in thermal shrinkage between 600°C and 900°C is preferably 10% or less. In this specification, the thermal shrinkage at a temperature (t°C) means the rate of change (%) of the dimension at t°C relative to the dimension (L0) before the start of measurement. Also, the thermal shrinkage at any temperature (t 1 ℃~t 2 The difference in thermal shrinkage at t 1 ℃~t 2 This refers to the difference between the maximum and minimum thermal shrinkage rates between temperatures in °C.
[0082] (Method of producing pellets for evaluation) The conductive paste is dried at 120°C for 40 minutes to obtain a dry conductive sheet. The obtained dry conductive sheet is pulverized to obtain a dry powder sample. 0.15 g of the obtained dry powder sample is placed in a cylindrical mold (bottom diameter 0.5 cm) and subjected to a pressure of 1000 kgf / cm 2 A pressure of 1.5 mm was applied to prepare a pellet for evaluation (diameter 5 mm × thickness 1.5 mm).
[0083] The evaluation pellets thus prepared were fired under nitrogen at 310°C for 3 hours, and then heated from 25°C to 1300°C at a rate of 5°C / min in a mixed gas atmosphere of nitrogen gas containing 0.15% hydrogen and water vapor gas, each with a gas flow rate of 200 ml / min, and the thermal shrinkage rate (dimensional change rate) was measured using a thermomechanical analyzer.
[0084] Here, the thermal shrinkage rate (rate of dimensional change) α at temperature t° C. is calculated by the following formula. α=100×(L0-L) / L0 L0: Height of test piece (evaluation pellet) before measurement L: Height of the test piece (evaluation pellet) at the time of measurement (temperature t°C)
[0085] Moreover, the difference in thermal shrinkage rate between 600°C and 900°C of the evaluation pellets produced using the conductive paste of this embodiment is more preferably 9% or less, further preferably 8% or less, and may be 7% or less. The lower limit of the thermal shrinkage difference is not particularly limited, and may be, for example, 1% or more, 2% or more, 4% or more, or 5% or more. If the lower limit of the thermal shrinkage difference is too low, the sintering behavior of the conductive film may be excessively delayed.
[0086] For example, the difference in thermal shrinkage rate of the evaluation pellets at 550°C or more and 750°C or less may be 7% or less, 6% or less, or 5% or less. The lower limit of the difference in thermal shrinkage rate is not particularly limited, but may be, for example, 0.5% or more. In a conductive paste manufactured under similar conditions except that it does not contain the phosphoric acid-based additive, the difference in thermal shrinkage rate at 550°C or more and 750°C or less exceeds 7%.
[0087] Also, for example, the difference in the thermal shrinkage rate of the evaluation pellets at 900° C. to 1200° C. may be 5% or more, or 7% or more. Since the thermal shrinkage of the dielectric layer (green sheet) increases sharply at around 1000° C., when the difference in the thermal shrinkage rate of the evaluation pellets at 900° C. to 1200° C. is within the above range, the thermal shrinkage behavior can be made close to that of the dielectric layer.
[0088] As described above, the conductive film using the conductive paste of this embodiment has a small difference in thermal shrinkage during sintering and thermally shrinks gently. In addition, the conductive paste of this embodiment has a final thermal shrinkage amount of the conductive film that is approximately the same as the final thermal shrinkage amount of the green sheet (thermal shrinkage rate: about 20%), so that the occurrence of delamination and cracks is well suppressed. For example, the difference in thermal shrinkage rate at 25°C to 1300°C of the evaluation pellet using the conductive paste of this embodiment may be, for example, 15% to 25%, or 17% to 23%. In addition, the difference in thermal shrinkage rate at 25°C to 1300°C of the green sheet used in the multilayer ceramic capacitor of this embodiment may also be the same as the range of the evaluation pellet.
[0089] (b) Sintering start temperature The sintering start temperature (thermal shrinkage start temperature) of the evaluation pellets produced using the conductive paste of this embodiment may be, for example, 500°C to 700°C, or 500°C to 650°C. The conductive paste of this embodiment has a relatively high thermal shrinkage start temperature compared to a conductive paste produced under similar conditions except that it does not contain a phosphoric acid-based additive. In addition, the conductive paste of this embodiment reduces the amount of change in the thermal shrinkage rate (dimensional change rate) from the start of sintering to about 900°C, for example, so that sintering proceeds slowly, thereby suppressing the occurrence of delamination and cracks. The thermal shrinkage start temperature refers to the temperature at which the thermal shrinkage rate becomes 5% in the thermal shrinkage curve.
[0090] [Multilayer ceramic capacitors] The conductive paste of the present embodiment can be suitably used in electronic components such as multilayer ceramic capacitors. The multilayer ceramic capacitor has, for example, dielectric layers formed using dielectric green sheets and internal electrode layers formed using the conductive paste.
[0091] Hereinafter, embodiments of the multilayer ceramic capacitor of the present invention will be described with reference to the drawings. In the drawings, the drawings may be represented diagrammatically or at a different scale as appropriate. The positions and directions of the members will be described with reference to an XYZ orthogonal coordinate system shown in FIG. 1 as appropriate. In this XYZ orthogonal coordinate system, the X and Y directions are horizontal directions, and the Z direction is vertical (up-down direction).
[0092] 1A and 1B are diagrams showing a multilayer ceramic capacitor 1. The multilayer ceramic capacitor 1 includes an external electrode 20 and a ceramic laminate 10 in which dielectric layers 12 and internal electrode layers 11 are alternately laminated.
[0093] A method for manufacturing a multilayer ceramic capacitor using the conductive paste will be described below. First, the conductive paste is screen-printed on a ceramic green sheet and dried to form a dry film. A plurality of ceramic green sheets having this dry film on the upper surface are laminated by pressure bonding to obtain a laminate, and the laminate is then fired and integrated to produce a ceramic laminate 10 in which internal electrode layers 11 and dielectric layers 12 are alternately laminated. Then, a pair of external electrodes 20 is formed on both ends of the ceramic laminate 10 to manufacture a multilayer ceramic capacitor 1. A more detailed description will be given below.
[0094] First, a green sheet, which is an unfired ceramic sheet, is prepared. For example, the green sheet is prepared by adding a binder resin such as polyvinyl butyral and an organic solvent such as terpineol to a raw powder of a specific ceramic such as barium titanate, applying the paste for the dielectric layer to a support film such as a PET film in a sheet form, and drying the paste to remove the solvent. The thickness of the dielectric layer made of the green sheet is not particularly limited, but is preferably 0.05 μm or more and 3 μm or less from the viewpoint of the demand for miniaturization of the multilayer ceramic capacitor.
[0095] Next, the conductive paste is printed and applied to one side of the green sheet, and then dried to form a dry film (conductive film) on one side of the green sheet to prepare a plurality of sheets. Note that, from the viewpoint of the requirement for thinning the internal electrode layer 11, the thickness of the dry film formed from the conductive paste is preferably 1 μm or less after drying. Next, the green sheet is peeled off from the support film, and the green sheet and the conductive film formed on one side thereof are laminated so as to be arranged alternately, and then a laminate is obtained by a heat and pressure treatment. Note that a configuration may be adopted in which protective ceramic green sheets not coated with conductive paste are further arranged on both sides of the laminate.
[0096] Next, the laminate is cut to a predetermined size to form green chips, and the green chips are subjected to a binder removal process and fired in a reducing atmosphere to produce a laminated ceramic fired body (ceramic laminate 10). The binder removal process is preferably performed in air or N2 gas. The temperature during the binder removal process is, for example, 200°C or higher and 400°C or lower. The temperature is preferably held for 0.5 hours or higher and 24 hours or lower during the binder removal process. The firing is performed in a reducing atmosphere to suppress oxidation of the metal used in the conductive film, and the temperature during firing of the laminate is, for example, 1000°C or higher and 1350°C or lower, and the temperature is held for, for example, 0.5 hours or higher and 8 hours or lower.
[0097] By firing the green chip, the organic binder in the ceramic green sheet is completely removed, and the ceramic raw material powder is fired to form the ceramic dielectric layer 12. The organic vehicle in the conductive film is also removed, and the nickel powder or the alloy powder mainly composed of nickel is sintered or melted and integrated to form the internal electrode layer 11, forming a multilayer ceramic sintered body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. Note that, from the viewpoint of taking oxygen into the dielectric layer to increase reliability and suppressing reoxidation of the internal electrodes, the sintered multilayer ceramic sintered body may be subjected to an annealing treatment.
[0098] A pair of external electrodes 20 are then provided on the produced fired laminated ceramic body to manufacture the laminated ceramic capacitor 1. For example, the external electrodes 20 include an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. The external electrodes 20 can be preferably made of, for example, copper, nickel, or an alloy thereof. The external electrodes 20 may be provided on the laminate before firing. The electronic component may be an electronic component other than a laminated ceramic capacitor. EXAMPLES
[0099] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to these examples.
[0100] [Evaluation method] (Evaluation of heat shrinkage behavior) (i) Preparation of pellets for evaluation The conductive paste of Example 1 obtained was dried at 120°C for 40 minutes, and the resulting dried conductive sheet was pulverized to obtain a dry powder sample. 0.15 g of the dry powder sample thus prepared was placed in a cylindrical mold (bottom diameter 0.5 cm) and subjected to a pressure of 1000 kgf / cm 2 A pressure of 1000 MPa was applied to prepare pellets for evaluation.
[0101] (ii) Measurement of thermal shrinkage behavior Next, the prepared evaluation pellets were fired at 310°C for 3 hours in a nitrogen atmosphere to perform a binder removal treatment. The binder removal behavior can be confirmed by TMA. Next, the evaluation pellets were returned to room temperature, and the thermal shrinkage curve was measured by TMA. Here, the sample was loaded with 10.0 g, and the atmosphere was a mixed gas of nitrogen gas containing 0.15% hydrogen and water vapor gas with a gas flow rate of 200 ml / min, the temperature rise rate was 5°C / min, and the measurement temperature range was 25°C to 1300°C. From the measurement data, the difference in thermal shrinkage rate at 600°C to 900°C was obtained. The evaluation results are shown in Table 1.
[0102] (Evaluation of film properties) The dispersibility of the conductive paste was evaluated by the following method.
[0103] A sample was printed (GAP thickness = 10 μm) on a glass substrate (2 inches) and dried. Drying was performed in an air atmosphere at a maximum temperature of 120 to 150 °C in a belt furnace. The dried film (2 cm x 2 cm, thickness 2 μm) obtained after drying was observed at ×100 (ocular, objective; each 10 times) using an optical microscope (Eclipse LV100D-U, Nikon Solutions Co., Ltd.) while shining light (backlight) from the back side of the glass substrate to confirm the presence or absence of lumps. When no lumps were observed, the dispersibility of the paste was judged to be good (◯), and when 1 or more lumps were observed, the dispersibility of the paste was judged to be poor (×).
[0104] (Seat Attack Evaluation) The sheet attack of the conductive paste was evaluated as follows: "Sheet attack" refers to a phenomenon in which the binder resin contained in the green sheet is dissolved by the components of the conductive paste, causing holes and wrinkles in the green sheet.
[0105] First, the conductive paste was screen-printed on the green sheet. A 325 mesh, 1.8 x 1.8 cm pattern screen was used for printing. After printing, the sheet was dried at 75°C for 10 minutes, and then the green sheet was checked from the back side (green sheet side) with an optical microscope (Eclipse LV100D-U, Nikon Solutions Co., Ltd.) to see if there were any holes or thinning due to dissolution and swelling. Evaluation was based on the following criteria. 〇: No holes or thinning were found in the green sheet. ×: Some holes or thinning were found in the green sheet.
[0106] (Surface roughness evaluation) The obtained conductive paste was applied to a glass substrate using an applicator to a wet film thickness of 10 μm and dried at 120°C for 10 minutes. The average surface roughness Sa (μm) of the obtained dried film was measured using a laser microscope (OLS-5000, Evident Co., Ltd.).
[0107] [Materials used] (conductive powder) As the conductive powder, Ni powder (SEM average particle size: 0.18 μm) was used.
[0108] (ceramic powder) Barium titanate (BaTiO3: SEM average particle size 0.05 μm) was used as the ceramic powder.
[0109] (binder resin) As the binder resin, ethyl cellulose resin (EC) and polyvinyl butyral resin (PVB) were used.
[0110] (Dispersant) In both the examples and the comparative examples, the dispersant contained in common was an acid dispersant, that is, a polycarboxylic acid dispersant having polyoxyalkylene as a graft chain.
[0111] (Additives) As the phosphoric acid-based additives, the following A-1, A-2, and A-3, and phosphoric acid were used. A-1: In the compound of formula (1), R 1 contains polyether and polyester groups, R 2 , R 3 Contains a phosphate additive in which is hydrogen (weight average molecular weight: about 1600). A-2: In the compound of formula (1), R 1 contains polyether and polyester groups, R 2 , R 3 The compound contains a phosphate additive in which the base is an alkylol ammonium salt (weight average molecular weight: about 1400). A-3: In the compound of formula (1), R 1 contains polyether and polyester groups, R 2 is hydrogen and R 3 The additive contains a phosphate group which is an alkyl ammonium base (weight average molecular weight: about 1800). A-4: In the compound of formula (1), R 1 contains an ether group having 6 or more carbon atoms, and R 2 , R 3 Contains a phosphate additive in which is hydrogen (weight average molecular weight: about 750).
[0112] As comparative examples, the following additives were used in place of the phosphoric acid-based additives used in the examples. Z: Oleoyl sarcosine G: Oxyethylene laurylamine
[0113] (Organic solvent) The organic solvents used were dihydroterpineol (DHT), mineral spirits (MSA), and diethylene glycol monobutyl ether acetate (BCA).
[0114] [Example 1] Conductive powder 50% by mass, ceramic powder 4% by mass, dispersant 0.15% by mass, phosphoric acid additive "A-1" 0.25% by mass, binder resin (EC:PVB=6:4 (mass ratio)) 3% by mass, organic solvent (DHT:MA=7:3 (mass ratio)) 42.6% by mass were added to make a total of 100% by mass, and these materials were mixed to prepare a conductive paste. The content of each material in the conductive paste and the evaluation results of the thermal shrinkage behavior are shown in Table 1 and Figure 2.
[0115] [Examples 2 to 14, Comparative Examples 1 to 5] Conductive pastes were prepared and evaluated in the same manner as in Example 1, except that the particle size of the conductive powder, the content of the ceramic powder, the content of the dispersant, the type and content of the additive, the type and content of the binder resin, and the type and content of the organic solvent were set as shown in Tables 1 to 3. The content of each material in the conductive paste and the evaluation results are shown in Tables 1 to 3.
[0116] [Table 1]
[0117] [Table 2]
[0118] [Table 3]
[0119] (Evaluation Results) Table 1 shows the evaluation results of the conductive pastes of Examples 1 to 9 and Comparative Examples 1 to 5, which were obtained by varying the type and content of additives, the type of binder resin, and the type of organic solvent. The conductive pastes of Examples 1 to 9 had smaller thermal shrinkage differences at 600°C to 900°C, did not produce lumps or sheet attack, and had smaller surface roughness, compared with the conductive pastes of Comparative Examples 1 to 3, which did not contain the phosphoric acid-based additive represented by formula (1). In the case of Comparative Example 4, which contained phosphoric acid as an additive, lumps were produced, and in the case of Comparative Example 5, which contained only terpineol (TPO, a terpene-based solvent) as the organic solvent, sheet attack occurred.
[0120] Moreover, in both Example 4, in which the binder resin is only EC, and Example 5, in which the binder resin is only PVB, the difference in thermal shrinkage can be made small.
[0121] Table 2 shows the evaluation results of conductive pastes of Examples 1, 9, and 10, in which the content of ceramic powder (BaTiO3) was changed. As shown in Example 10 in Table 2, a large content of ceramic powder can further suppress the thermal shrinkage of the internal electrode layer (compare Example 1 and Example 9 in Table 2). Also, as shown in Examples 11 and 12 in Table 2, it can be seen that rapid thermal shrinkage can be suppressed even if the content of ceramic powder is reduced.
[0122] Table 3 shows the evaluation results of the conductive pastes of Examples 1, 13, and 14, in which the particle size of the conductive powder (Ni powder) was changed. From Table 3, it can be seen that the larger the particle size of the Ni powder, the smaller the thermal shrinkage difference, but even in Example 14, in which the particle size is small, the thermal shrinkage difference can be sufficiently reduced.
[0123] The thermal shrinkage curve of the evaluation pellets of Example 1 is shown in Figure 2. As shown in Figure 2, in the case of the evaluation pellets of Example 1, the thermal shrinkage starting temperature at which the thermal shrinkage rate (dimensional change rate) becomes 5% is relatively low at 550°C. However, in the temperature range of 550°C to 750°C, the thermal shrinkage curve is upwardly convex, and the thermal shrinkage difference, i.e., the degree of shrinkage, is small. Moreover, in the temperature range of 600°C to 900°C, the thermal shrinkage curve is generally upwardly convex, and particularly in the temperature range of 800°C to 900°C, the thermal shrinkage difference is small.
[0124] Fig. 3 shows an image of a cross section of the evaluation pellets of Example 1 taken by a SEM (scanning electron microscope) at 800°C, and Fig. 4 shows an image of a cross section of the evaluation pellets of Comparative Example 1 taken by a SEM at 800°C. It was confirmed that the evaluation pellets of Example 1 (Fig. 3) had more voids at 800°C in the firing process and sintering proceeded more slowly than the evaluation pellets of Comparative Example 1 (Fig. 4). [Industrial Applicability]
[0125] When the conductive paste of the present invention is used to form an internal electrode of a multilayer ceramic capacitor, a highly reliable multilayer ceramic capacitor can be obtained with high productivity. Therefore, the conductive paste of the present invention can be suitably used for the internal electrodes of multilayer ceramic capacitors, which are chip components of electronic devices such as mobile phones and digital devices that are becoming increasingly smaller.
[0126] The technical scope of the present invention is not limited to the aspects described in the above-mentioned embodiments. One or more of the requirements described in the above-mentioned embodiments may be omitted. The requirements described in the above-mentioned embodiments may be combined as appropriate. In addition, to the extent permitted by law, the disclosures of all documents cited in the above-mentioned embodiments are incorporated by reference and made part of the description in this text. [Explanation of symbols]
[0127] 1. Multilayer ceramic capacitors 10 Ceramic laminate 11 Internal electrode layer 12 Dielectric layer 20 External electrode 21 External electrode layer 22 Plating layer
Claims
1. A conductive paste comprising a conductive powder, a ceramic powder, an additive, a binder resin and an organic solvent, The additive contains a phosphoric acid-based additive having a structure represented by the following structural formula (1) in an amount of 0.03 mass % to 1.5 mass % based on the total amount of the conductive paste, The organic solvent includes a terpene-based solvent (a) and at least one solvent (b) selected from a hydrocarbon-based solvent, an acetate-based solvent, an ether-based solvent, and a ketone-based solvent; The conductive paste, wherein the binder resin includes at least one of a cellulose-based resin and an acetal-based resin. 【Chemistry 1】 (However, R 1 contains at least one of an alkyl group having 6 or more carbon atoms, an ether group having 6 or more carbon atoms, a polyether group, and a polyester group; R 2 , R 3 are each independently hydrogen or an ammonium salt group, or contain at least one of an alkyl group, an ester group, and an ether group.
2. The conductive paste according to claim 1 , wherein the conductive powder has an average particle size of 0.05 μm or more and 1.0 μm or less.
3. The conductive paste according to claim 1 or 2, wherein the conductive powder contains at least one metal powder selected from the group consisting of Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof.
4. The conductive paste according to claim 1 , wherein the ceramic powder is contained in an amount of 1 mass % or more based on the total amount of the conductive paste.
5. The conductive paste according to claim 1 or 2, wherein the ceramic powder contains barium titanate.
6. The conductive paste according to claim 5 , wherein the ceramic powder has an average particle size of 0.01 μm or more and 0.5 μm or less.
7. The conductive paste according to claim 1 or 2, further comprising an acidic dispersant or a basic dispersant.
8. 3. The conductive paste according to claim 1, which is for use in an internal electrode of a multilayer ceramic part.
9. An electronic component formed by using the conductive paste according to claim 1 or 2.
10. The laminate has at least a dielectric layer and an internal electrode layer stacked thereon, 9. A multilayer ceramic capacitor, wherein the internal electrode layers are formed using the conductive paste according to claim 8.
Citation Information
Patent Citations
Nickel fine particle-containing composition and method for producing the same
JP2014145117A
Core-shell particle and composition for conductor formation
JP2016014194A